To what extent are Canadian second language policies evidence-based? Reflections on the intersections of research and policy - Cummins, Jim (Frontiers in Psychology, 2014)
The paper addresses the intersections between research, ideology, and Canadian educational policies focusing on four major areas: (a) core and immersion programs for the teaching of French to Anglophone students, (b) policies concerning the learning of English and French by students from immigrant backgrounds, (c) heritage language teaching, and (d) the education of Deaf and hard-of hearing students. With respect to the teaching of French, policy-makers have largely ignored the fact that most core French programs produce meager results for the vast majority of students. Only a small proportion of students (< 10%) attend more effective alternatives (e.g. French immersion and Intensive French programs). With respect to immigrant-background students, a large majority of teachers and administrators have not had opportunities to access the knowledge base regarding effective instruction for these students nor have they had opportunities for pre-service or in-service professional development regarding effective instructional practices. Educational policies have also treated the linguistic resources that children bring to school with, at best, benign neglect. In some cases (e.g., Ontario) school systems have been explicitly prohibited from instituting enrichment bilingual programs that would promote students’ bilingualism and biliteracy. Finally, with respect to Deaf students, policy-makers have ignored overwhelming research on the positive relationship between academic success and the development of proficiency in natural sign languages, preferring instead to perpetuate the falsehood that acquisition of languages such as American Sign Language by young children (with or without cochlear implants) will impede children’s language and academic development. The paper reviews the kinds of policies, programs, and practices that could be implemented (at no additional cost) if policy-makers and educators pursued evidence-based educational policies.